Differential effects of location and object overlap on new learning - Chaloupka, Benjamin; Zeithamova, Dagmar (Frontiers in Cognition, 2024)
Overlap with prior experience facilitates learning in some cases while hindering it in others. As facilitation and interference are typically studied in separate lines of research, using distinct paradigms, it is unclear what key factors drive the opposing behavioral outcomes. In two experiments, we tested whether both effects can be observed within a single task, depending on what overlaps between experiences. Participants completed a novel task in which they learned a grid of object-location associations, followed by a second grid that overlapped with the first in locations and/or objects. We hypothesized that overlap of locations would serve as a spatial schema, facilitating new learning, while overlap of objects would create interference. In line with our hypothesis, we found that location overlap facilitated learning of the second grid, while object overlap hindered learning of the second grid. We replicated these findings in a second experiment, additionally showing that both effects remain largely stable across two distinct grid shapes. These results demonstrate that the effect of overlap can be manipulated within a single task, pinpointing one factor that determines the direction of the effect, and highlighting the differential roles of 'what' and 'where' in the organization of memory.